2012
DOI: 10.1590/s0100-40422012000200003
|View full text |Cite
|
Sign up to set email alerts
|

Bases moleculares da ação anti-inflamatória dos ácidos oleanólico e ursólico sobre as isoformas da ciclo-oxigenase por docking e dinâmica molecular

Abstract: Recebido em 28/10/10; aceito em 11/7/11; publicado na web em 2/9/11 THE MOLECULAR BASIS OF ANTI-INFLAMMATORY ACTION OF THE OLEANOLIC AND URSOLIC ACIDS ON CYCLOOXYGENASE ISOFORMS BY DOCKING AND MOLECULAR DYNAMICS. The triterpenoids oleanolic (OA) and ursolic (UA) acids show non-selective antiinflamatory activity in vitro for cyclooxygenase (COX) isoforms. 3D conformations of OA and UA, with three possible orientations (1, 1' and 2) in the active site of isoforms COX, obtained by docking, were submitted to molec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…The inhibitors selected may have an equivalent affinity in relation to the selected control compounds. The interaction with Ser 353 in Z-814 demonstrates the possibility of a binding activity associated with low IC 50 values [ 28 , 29 , 30 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The inhibitors selected may have an equivalent affinity in relation to the selected control compounds. The interaction with Ser 353 in Z-814 demonstrates the possibility of a binding activity associated with low IC 50 values [ 28 , 29 , 30 ].…”
Section: Resultsmentioning
confidence: 99%
“…The calculation of binding affinity (∆G) was also performed in order to compare the actual data obtained and the values predicted in silico, which was the same methodology adopted by Santos et al, 2020 [ 14 ], according to Equation (5). where R (gas constant) is 1.987.10 −3 kcal·mol −1 ·K −1 , the temperature is 310 K for rofecoxib/celecoxib, and K i is 310.10 −9 M for rofecoxib and 340.10 −9 M for celecoxib [ 28 , 32 , 52 ].…”
Section: Methodsmentioning
confidence: 99%
“…Because UA has exhibited this feature (multi-targets), it may be considered an advantage over other compounds described in the literature. Verano et al ( 2013 ) has shown that UA 10 mg/kg (i.p) has an antinociceptive effect, so we chose this dose to test its effect orally and have confirmed the antinociceptive and anti-inflammatory effects of UA through inhibitions of the TRPV1 receptor and serotonergic synergism (5-HT); reduced IL-2, IL-6, interferon (IFN)-γ, TNF-α, reactive oxygen species (ROS), phospholipase A2 and NF-κβ release; reduced COX-2 and inducible nitric oxide synthase (iNOS) expression; (Kashyap et al, 2016 ) and favorable interactions for complexes formed with COX-1 and COX-2 (Magalhães et al, 2012 ). Zhang et al ( 2013 ) demonstrated that UA can induce apoptosis of cancer cells by reducing COX-2 expression and Ma et al ( 2014 ) demonstrated that UA reduced COX-2 expression in CCl 4 -treated animals.…”
Section: Discussionmentioning
confidence: 99%
“…Õ software 27 and molecular docking was performed using AutoDock 4 Õ software 27,28 . Lamarckian genetic algorithms were used as search parameter to find the best conformation assumed by each docking ligand in a total of 50 energy assessment (generations) 27 .…”
Section: In Silico Assaysmentioning
confidence: 99%
“…Lamarckian genetic algorithms were used as search parameter to find the best conformation assumed by each docking ligand in a total of 50 energy assessment (generations) 27 . The enzyme structure was kept rigid and the ligands were kept with maximum allowed flexibility.…”
Section: In Silico Assaysmentioning
confidence: 99%